PENGARUH PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) BERBASIS ETNOMATEMATIKA TERHADAP PEMAHAMAN KONSEP LINGKARAN SISWA KELAS VI SDN LAMPEUNEURUT ACEH BESAR - Sukira Humaira; Linda Vitoria; Mislinawati (STKIP Subang, 2026)
This study is motivated by students’ low understanding of mathematical concepts, particularly in circle material, which is caused by learning processes that are not yet fully contextual and do not actively engage students. This study aims to determine the effect of the ethnomathematics-based Realistic Mathematics Education (RME) approach on grade VI students’ understanding of circle concepts at SDN Lampeuneurut Aceh Besar. This study employed a quantitative approach with a quasi-experimental design using a nonequivalent control group design. The research population consisted of all grade VI students at SDN Lampeuneurut, with the sample comprising two classes, namely the experimental class and the control class, selected using purposive sampling. The research instrument was a 10-item essay test administered in the form of pretest and posttest. Data were analyzed using SPSS version 31 with an independent sample t-test. The results showed a significance value (2-tailed) < 0.001 < 0.05, indicating that Ha was accepted and H0 was rejected. Therefore, it can be concluded that the ethnomathematics-based Realistic Mathematics Education (RME) approach has a significant effect on grade VI students’ understanding of circle concepts at SDN Lampeuneurut Aceh Besar.